Phytosanitary irradiation of three species of spider mites (Trombidiformes: Tetranychidae). Issue 2 (29th January 2018) - Nicholas, Adrian; Lidbetter, Fiona; Eagleton, Nyet; Spohr, Lorraine; Harris, Anne; Barchia, Idris
Abstract: The survival of three species of Tetranychidae mites: Tetranychus evansi (tomato red spider mite), Tetranychus ludeni (bean spider mite) and Tetranychus urticae (two‐spotted mite), exposed to gamma irradiation doses of 200, 300, 400, 500 and 600 Gy was investigated. The aim was to identify an irradiation dose capable of killing or sterilising mites infesting horticultural produce to prevent movement to and colonisation of host plants in non‐infested regions or countries. Eggs were irradiated separately; otherwise, to simulate naturally occurring mite populations, mixed life stages (immatures and adults) were combined and the treatment effects compared to non‐irradiated controls. Irradiated eggs of all species failed to develop and hatch at 200 Gy and above. Tetranychus urticae was the most tolerant species, requiring an irradiation dose of 300 Gy to ensure all adult females were sterilised. Sterilised adults continued to lay eggs, but these eggs failed to develop or hatch. Tetranychus evansi and T. ludeni were sterilised when irradiated at 200 Gy. Based on these results, a dose of 300 Gy is recommended as a phytosanitary measure to prevent the survival of these species of Tetranychidae pests of horticultural produce in non‐infested regions. Combined with data from other studies this study proposes a generic dose for Tetranychidae mites of 375 Gy.